A Qualitative Study on the Breastfeeding Experiences of Young Mothers - Astuti, Andari Wuri; Kurniawati, Herlin Fitriana; Kurniawati, Herlin Fitriani (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Breastfeeding practice for young mothers could be problematic, especially when supports are absent. Evidence reported that young mothers have risks of experiencing mental health problems and of behavioural problems in their children. Data showed that 36 per 1,000 childbirth occurred among Indonesian female adolescents aged 15-19 during 2018. Nevertheless, the breastfeeding experience of young mothers has not been well studied, particularly in the Indonesian context. Therefore, to develop professional caring and supporting relationships, it is important to address this knowledge gap.Purpose: This study aimed to explore the experiences of breastfeeding practices among Indonesian young mothers.Methods: A qualitative exploratory study was employed, and one-to-one in-depth interviews were conducted on 18 young mothers between May until August 2019. Data analysis was guided by Colaizziâ€™s thematic approach.Results: Four key themes emerged from the qualitative data, i.e., formal support of breastfeeding, the role of family, partner and peers, culture and judgement, and future aspirations and healthcare. Indonesian young mothers sought formal information on breastfeeding from healthcare providers. However, there was a lack of translation into practices due to lack of supports from partners, cultural beliefs, and parents' interference, which consequently led to the failure of breastfeeding. Indonesian young mothers were suggesting that breastfeeding information should also be provided to their circle of supports, such as partners and close relatives. Conclusion: Indonesian young mothers experienced complex situations through their journey of breastfeeding practices. A tailored maternity health service involving partners, parents, and communities into culture-sensitive programme intervention is needed to provide professional caring, and reliable supportive sources of breastfeeding for young mothers.Â